2022
DOI: 10.1128/spectrum.01454-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elexacaftor/Tezacaftor/Ivacaftor Therapy on the Cystic Fibrosis Airway Microbial Metagenome

Abstract: Shotgun metagenome sequencing of respiratory secretions with spike-in controls for normalization demonstrated that 1 year of high-efficient CFTR modulation with elexacaftor/tezacaftor/ivacaftor extensively reduced the bacterial load. Longer observation periods will be necessary to resolve whether the partial reversion of the basic defect that is achieved with ELX/TEZ/IVA is sufficient in the long run to render the CF lungs robust against the recolonization with common opportunistic pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 81 publications
1
12
1
1
Order By: Relevance
“…Neither monotherapy with IVA nor dual LUM/IVA changed the infection epidemiology in CF, but ELX/TEZ/IVA initiation was associated with a rapid reduction in infection-related visits and antimicrobial use among pwCF ( Miller et al, 2022 ). After 12-month of treatment with ELX/TEZ/IVA, the detection of Staphylococcus aureus and Pseudomonas aeruginosa decreased at single CF centers by 40% or more ( Pallenberg et al, 2022b ; Beck et al, 2023 ; Sheikh et al, 2023 ). Sputum microbiome diversity increased ( Sosinski et al, 2022 ).…”
Section: Immunology and Airway Microbiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Neither monotherapy with IVA nor dual LUM/IVA changed the infection epidemiology in CF, but ELX/TEZ/IVA initiation was associated with a rapid reduction in infection-related visits and antimicrobial use among pwCF ( Miller et al, 2022 ). After 12-month of treatment with ELX/TEZ/IVA, the detection of Staphylococcus aureus and Pseudomonas aeruginosa decreased at single CF centers by 40% or more ( Pallenberg et al, 2022b ; Beck et al, 2023 ; Sheikh et al, 2023 ). Sputum microbiome diversity increased ( Sosinski et al, 2022 ).…”
Section: Immunology and Airway Microbiologymentioning
confidence: 99%
“…However, the microbial network remained vulnerable to fragmentation. The initial shift of the CF airway microbiome was attributable to the ELX/TEZ/IVA-mediated gain of CFTR activity followed by a diversification driven by a group of commensals at the 1-year time point that are typical for healthy airways ( Pallenberg et al, 2022b ).…”
Section: Immunology and Airway Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…IVA treatment showed an initial reduction in the prevalence of bacterial isolation, but P. aeruginosa density rebounded after 1 year ( 16 ), and P. aeruginosa strains present before treatment were found to persist even after intensive antibiotic therapy ( 17 ). Recent studies based on airway microbial metagenomic sequencing showed that ETI combination therapy reduced the load of P. aeruginosa and S. aureus in both mild and severe CF patients ( 18 ). This microbiological shift is attributable to the ETI-mediated gain of CFTR activity and the possible effect on the airway microbiota that is converted into a community of commensals.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that this level of rescue of F508del-CFTR function achieved by ELX/TEZ/IVA leads to substantial improvement in airway mucus obstruction, as evidenced by reduced mucus plugging detected by magnetic resonance imaging and improved ventilation homogeneity detected by multiple-breath washout [14]. However, the effects of ELX/TEZ/IVA on abnormal viscoelasticity of airway mucus and chronic inflammation in patients with CF have not been studied, and data of effects on the sputum microbiome remain limited [21,22].…”
Section: Introductionmentioning
confidence: 99%